2005
DOI: 10.1007/s10654-004-7537-9
|View full text |Cite
|
Sign up to set email alerts
|

Community-based study of cataracts among type 2 diabetics in Kinmen

Abstract: The purpose of this study was to assess the prevalence and risk factors of each type of cataract among type 2 diabetics in Kinmen, Taiwan. There were 971 type 2 diabetics ascertained from a community-based mass screening between 1991 and 1993. In 1999, a total of 578 (59.5%) patients with type 2 diabetes were examined with an eye screening performed by two senior ophthalmologists using a 45-degree thin slit-lamp biomicroscopy and ophthalmoscopy to examine the lens after dilating the pupils. The overall prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…By contrast, blood pressure was inconsistently associated with cataract in two observational studies. Becker et al found hypertension increased, while Tung et al found diastolic blood pressure ≥ 90 mmHg (after adjusting for blood pressure lowering medication) decreased, the odds of cataract . There was no association in the other observational studies.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…By contrast, blood pressure was inconsistently associated with cataract in two observational studies. Becker et al found hypertension increased, while Tung et al found diastolic blood pressure ≥ 90 mmHg (after adjusting for blood pressure lowering medication) decreased, the odds of cataract . There was no association in the other observational studies.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, Janghorbani and Amini found that oral agents were protective but used diabetes treatment at the latest clinic visit in their analysis . Six observational studies did not include diabetes treatment as a variable in the modelling . Two other studies identified diabetes treatment as a covariate.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations